The significance of single-cell transcriptome analysis in epididymis research - Liu, Meng-Meng; Feng, Xin-Lei; Qi, Chao; Zhang, Shu-Er; Zhang, Guo-Liang (Frontiers in Cell and Developmental Biology, 2024)
As a crucial component of the male reproductive system, the epididymis plays multiple roles, including sperm storage and secretion of nutritive fluids for sperm development and maturation. The acquisition of fertilization capacity by sperm occurs during their transport through the epididymis. Compared with the testis, little has been realized about the importance of the epididymis. However, with the development of molecular biology and single-cell sequencing technology, the importance of the epididymis for male fertility should be reconsidered. Recent studies have revealed that different regions of the epididymis exhibit distinct functions and cell type compositions, which are likely determined by variations in gene expression patterns. In this review, we primarily focused on elucidating the cellular composition and region-specific gene expression patterns within different segments of the epididymis and provided detailed insights into epididymal function in male fertility. 1 设置了格式: 字体: (中文) 宋体, (中文) 简体中文(中国大陆)